Overview of the Evolution of Insolvency Companies in Romania - Veronica GROSU; Ancuta A. CHELBA (Communications of International Proceedings, 2021)
The purpose of this paper is to analyze the context in which the factors determined in the bankruptcy of economic entities maintain their level of influence in the current health crisis. This goal was proposed especially because the health crisis has significantly affected certain areas or positively stimulated the activity and performances of other economic sectors. In order to identify these factors and establish the existing relations of influence between them and the insolvency of economic operators, we have established two main objectives. The first objective consists in the contextual analysis of the evolution of the bankruptcies and insolvency of the companies in the period before COVID and the current period in Romania. The second objective aims to identify the existing relations between the evolution of the number of insolvent companies and the evolution of GDP in Romania. The obtained results consist in the national mapping of the way in which the situation of the insolvent companies evolved, in the period when the national economy was not affected by the repercussions of the current pandemic; another result is the identification of potential triggers that Romanian companies have not faced before (such as, for example, the health crisis - a new factor of influence for companies); but especially the obtained results were materialized in an econometric model for establishing the correlations between the macroeconomic variable GDP and the dynamics of the number of companies in insolvency in period 2010-2020.
Keywords: Insolvency; Bankruptcy; GDP; Enterprise Crisis.